CYBER HOSTILITIES: CIVILIAN DIRECT PARTICIPATION - Dan-Iulian VOITAȘEC (Challenges of the Knowledge Society)
The manner in which hostilities are being conducted has changed in recent years. The battle field has transpired beyond the physical realm and now has a virtual component. Because of this, it is now easier than ever for civilians to get involved in hostilities. International Humanitarian Law applies to all situations of armed conflict and according to the principle of distinction, the parties to the conflict must, at all times, distinguish between civilians and combatants. The problem arises when the line between combatants and civilians starts to get blurry. Direct civilian participation in hostilities has been addressed in both Additional Protocols to the Geneva Conventions of 1949 and in 2009 the International Committee of the Red Cross published the Interpretive guidance on the notion of Direct Participation in Hostilities under international humanitarian law. Another document that addresses the problem of civilian direct participation is the Tallinn Manual on the International Law Applicable to Cyber Warfare prepared by an international group of experts at the invitation of the NATO Cooperative Cyber Defence Centre of Excellence in 2013. The guide prepared by the ICRC addresses the problem of civilian direct participation during conventional situations of armed conflict, while the Tallinn Manual addresses direct participation in situations of cyber warfare. The purpose of this paper is to study the application of civilian direct participation to situations of cyber warfare.